Numerical optimization of writing computer-generated holograms in threshold media - Makowski, Michal; Sadowski, Mateusz (Photonics Letters of Poland, 2021)
Recent developments in binary photo-magnetic materials showed efficient and ultra-fast rewriting of holograms where the intensity threshold allows for a dense, sub-diffraction limit packing of hologram points. This paper describes the numerical optimization of the process of writing and reconstructing of 2-D images in a binary-phase computer-generated holograms stored in the said threshold-like medium. Global optimization of the free parameters of the writing process is shown, including the intensity threshold level, propagation distance, hologram spot size and the shape of the boundary regions of the written spots. We present the optimal set of parameters for the best possible writing quality. Full Text: PDF References A. Stupakiewicz, K. Szerenos, D. Afanasiev et al., "Ultrafast nonthermal photo-magnetic recording in a transparent medium", Nature 542, 71 (2017). CrossRef J. Starobrat, A. Frej, J. Bolek, R. Trybus, A. Stupakiewicz, and M. Makowski, "Photo-magnetic recording of randomized holographic diffraction patterns in a transparent medium", Opt. Lett. 45, 5177 (2020). CrossRef V. Ostroverkhov, et al., "Micro-Holographic Storage and Threshold Holographic Recording Materials", Jap. J. App. Phys. 48.3S1, 03A035 (2009). CrossRef K. Matsushima, T. Shimobaba, "Band-Limited Angular Spectrum Method for Numerical Simulation of Free-Space Propagation in Far and Near Fields", Opt. Express 17, 19662 (2009). CrossRef F. Wyrowski, O. Bryngdahl, "Iterative Fourier-transform algorithm applied to computer holography", JOSA A 5.7, 1058 (1988). CrossRef I. Ducin, T. Shimobaba, M. Makowski, K. Kakarenko, A. Kowalczyk, Jaroslaw Suszek, M. Bieda, A. Kolodziejczyk, M. Sypek, "Holographic projection of images with step-less zoom and noise suppression by pixel separation", Opt. Comm. 340, 131 (2015). CrossRef M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation", Opt. Express 21, 29205 (2013). CrossRef